Genotyping of Burkholderia mallei from an outbreak of glanders in Bahrain suggests multiple introduction events. - Holger C Scholz; Talima Pearson; Heidie Hornstra; Michaela Projahn; Rahime Terzioglu; Renate Wernery; Enrico Georgi; Julia M Riehm; David M Wagner; Paul S Keim; Marina Joseph; Bobby Johnson; et al. (Public Library of Science (PLoS), 2014)
Background Glanders, caused by the gram-negative bacterium Burkholderia mallei, is a highly infectious zoonotic disease of solipeds causing severe disease in animals and men. Although eradicated from many Western countries, it recently emerged in Asia, the Middle-East, Africa, and South America. Due to its rareness, little is known about outbreak dynamics of the disease and its epidemiology. Methodology/principal findings We investigated a recent outbreak of glanders in Bahrain by applying high resolution genotyping (multiple locus variable number of tandem repeats, MLVA) and comparative whole genome sequencing to B. mallei isolated from infected horses and a camel. These results were compared to samples obtained from an outbreak in the United Arab Emirates in 2004, and further placed into a broader phylogeographic context based on previously published B. mallei data. The samples from the outbreak in Bahrain separated into two distinct clusters, suggesting a complex epidemiological background and evidence for the involvement of multiple B. mallei strains. Additionally, the samples from Bahrain were more closely related to B. mallei isolated from horses in the United Arab Emirates in 2004 than other B. mallei which is suggestive of repeated importation to the region from similar geographic sources. Conclusion/significance High-resolution genotyping and comparative whole genome analysis revealed the same phylogenetic patterns among our samples. The close relationship of the Dubai/UAE B. mallei populations to each other may be indicative of a similar geographic origin that has yet to be identified for the infecting strains. The recent emergence of glanders in combination with worldwide horse trading might pose a new risk for human infections.